Konsistensi Penyajian Laporan Keuangan dan Implikasinya (Studi Kasus pada Industri Pertambangan di BEI) - Ciputra, Lokky (Widya Mandala Surabaya Catholic University, 2011)
Financial statements are an integrated report, which used by company's management as a tools to present useful financial information. One of them is to get additional fund from the investor. In order to make the information useful, consistency as a base of comparability must be applied, which relevancy must be watched. Mining industries has been chosen because their high risk and indeterminancy nature. This study aims to give an opinion of consistency concepts in evaluate the mining's industry financial statements, which firing listed on the Indonesia Stock Exchange in 2007-2009. This study use descriptive-comparative method, which used 13 sample companies and selected by using purposive sampling method. Source of data is secondary data consisting audited Financial. Data were analyzed by compare 2007-2009 financial statement, analyze the cause of changes and grouping the analysis results. The results of the study show that all of the company applied consistency on their Financial statement presentation, although accounting changes like restatement and account reclassification happened. T hat indicate a consistency isn't always static, but sometime changes needed to improve relevancy and comparability of financial information.